@Indonesiatanpafeminis.id as a Challenge of Feminist Movement in Virtual Space - Maryani, Eni; Janitra, Preciosa Alnashava; Ratmita, Reksa Anggia (Frontiers in Sociology, 2021)
The fast-growing social media in Indonesia has opened up opportunities for spreading feminist ideas to a wider and more diverse audience. Various social media accounts especially Instagram that focus on gender advocacy and feminism such as @indonesiafeminis, @lawanpatriarki, and @feminismanis have developed in Indonesia. However, the development of the social media platform also presents groups that oppose feminists. One of the accounts of women’s groups that oppose feminists is @indonesiatanpafeminis.id (@indonesiawithoutfeminist.id). The research objectives are namely to analyze the diversity of issues and reveal the discourse contestation that developed in the @indonesiatanpafeminis.id, and dynamic relationships on the online and offline spaces between groups of feminists and anti-feminists or the other interest. This research employed the digital ethnography method that utilized observation, interview, and literature study as data collection techniques. This study found that the online conversations at @indonesiatanpafeminis.id revealed misconceptions on feminism from a group of women with a religious identity. Furthermore, the conversation also tends to strengthen patriarchal values with religious arguments that are gender-biased. However, the @indonesiatanpafeminis.id serves as a public space for open debates and education on feminist issues. The anti-feminist group behind the @indonesiatanpafeminis.id are women who identify themselves in a certain Muslim circle that has political, cultural, and religious agendas. One of the agendas is to influence the public to reject the Sexual Violence Eradication Bill. This study also noted the Muslim supporters of anti-feminism in Indonesia are less popular compared to progressive religious-based Muslim women organizations such as Aisyiyah (Muhammadiyah), Muslimat NU (Nahdlatul Ulama), and Rahima (Center for Education and Information on Islam and Women’s Rights). The study also evokes discussion on how the feminist and anti-feminist discourses can be utilized to criticize and develop the women’s movement or feminism in a multicultural context.